Where Capacity is Not the Only Problem : Moving from Generic Capacity Building to Support for Issues-Based Change in Nigeria - Pycroft, Christopher; Butterworth, Richard (World Bank, Washington, DC, 2012)
This brief highlights DFID's experience in Nigeria in adopting an issues-based approach in which its role lies more in responding to and following, rather than leading, local change processes. This shifts the donor's role to engaging with a wider variety of stakeholders, identifying groups and coalitions that are most likely to drive and achieve institutional changes that can alleviate poverty, and to designing innovative means of supporting such locally driven efforts. The paper comes to the conclusion that in environments where weak capacity is compounded by an absence of broad-based political will, donors need to develop new approaches. Development assistance that does not engage with the politics of institutional constraints, but focuses only on organizational capacity, will have limited impact in addressing poverty and may be counter-productive.